A Group-Randomized Study Comparing the Traditional Lecture and Informal Cooperative Learning For Undergraduate Radiology Training In A Malaysian University - Ibrahim, Mohd Salami; Mat Jusog, Norhasiza; Mohd Amen Rebuan, Husbani; Thwe Aung, Myat Moe; Cheah, Wai-hun; Esa, Abdul Rahman (IIUM Medical Journal Malaysia, 2022)
Purpose: Radiology teaching via the traditional lecture (TL) is susceptible to a decline in focus and engagement, leading to compromised training and competency. In this study, we investigated the teaching of radiology topics via informal cooperative learning (ICL). Materials and Methods: We randomly delivered teaching via the TL or the ICL to four clinical group of thirteen third-year undergraduate medical students. The study involved eleven radiology topics throughout one academic year. For each topic, two groups underwent the TL while the other two learned via the ICL. All students underwent a pre-test at the beginning of each class, consist of One Best Answer (OBA) and Objectively Structured Clinical Examination (OSCE) to assess knowledge and skills, respectively. They subsequently underwent post-tests with another OBA and OSCE assessments at the end of class and six weeks later. Results: Students who learned from the ICL classes scored significantly higher in the knowledge assessment immediately post-teaching, six weeks later, and the overall score regardless of time. Assessments of skills showed no statistically significant difference between the two teaching methods. However, for both the ICL and TL, post-teaching scores of knowledge and post-teaching scores of skills were significantly higher than the pre-test. Conclusion: Our study provides empirical evidence on the superior competency of undergraduate radiological skills through the ICL. The findings signify the need to engineer competent doctors via innovative clinical training. The novel experience from this study better-orientate radiology teaching and contribute to the broader field of medical education, clinical practice, and patient safety.